2010
DOI: 10.1111/j.1537-2995.2010.02753.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a rapid emergency hemorrhage panel

Abstract: Limiting EHPs to bleeding patients and modifications to the process and assays used for hemostasis testing lead to TATs of less than 20 minutes for critical testing in the clinical laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 16 publications
(26 reference statements)
0
46
0
Order By: Relevance
“…One typical source of increased turnaround time in most clinical laboratories is checking samples for hemolysis and clotting followed by rejection of the sample if either of these are found, even though these checks are seldom performed for point-of-care or whole-blood viscoelastic testing. In one study, hemolysis was shown to have no clinically significant effect on the PT or fibrinogen [4]. Clotted samples were rare (1.1%) and shortened the PT by only 0.7 s. Clotted samples lowered fibrinogen on average 18%, but resulted in only one of 2300 samples changing from normal to low fibrinogen.…”
Section: Standard Assaysmentioning
confidence: 99%
See 3 more Smart Citations
“…One typical source of increased turnaround time in most clinical laboratories is checking samples for hemolysis and clotting followed by rejection of the sample if either of these are found, even though these checks are seldom performed for point-of-care or whole-blood viscoelastic testing. In one study, hemolysis was shown to have no clinically significant effect on the PT or fibrinogen [4]. Clotted samples were rare (1.1%) and shortened the PT by only 0.7 s. Clotted samples lowered fibrinogen on average 18%, but resulted in only one of 2300 samples changing from normal to low fibrinogen.…”
Section: Standard Assaysmentioning
confidence: 99%
“…In a trauma situation, for example, where stabilization of the patient in the first hour is critical, turnaround times of nearly an hour may be almost useless even if very accurate. One approach for improving the speed of critical hemostasis results using a central coagulation laboratory is development of a specific emergency hemorrhage panel [4]. This may require revision of the entire approach to performing the testing in the clinical laboratory including bypassing login, minimizing specimen checking and retesting, and modification of test processing and testing protocols to reduce the time required.…”
Section: Standard Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Prior to the EHP, turnaround times for coagulation panels were 35 Ϯ 37 minutes. By ensuring sample prioritization in work queues, streamlining pre-analytical sample processing and adjustment of calibration curves, the turnaround time was reduced to 14 Ϯ 3 minutes.…”
Section: Coagulation Testing In Postpartum Hemorrhagementioning
confidence: 99%